2010
DOI: 10.1007/s00246-010-9709-6
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Epidemiology of Pediatric Endocarditis at a Children’s Hospital Over Seven Decades

Abstract: This study sought to determine whether improvements in the care of children with congenital heart disease (CHD) have changed the epidemiology of infective endocarditis (IE). A retrospective study of patients 18 years of age and younger treated for IE from 1992 to 2004 (era 3) was conducted at the authors' children's hospital in New York City. This study was compared with two previous studies conducted at the same hospital from 1930 to 1959 (era 1) and from 1977 to 1992 (era 2). During the three eras, IE was di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
90
0
8

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(111 citation statements)
references
References 40 publications
13
90
0
8
Order By: Relevance
“…1,4,[9][10][11] In our study, there was only 1 case of Enterococcus faecalis endocarditis (2%), compared with 7% to 16% reported in other series. 4,9,11 This may be due to the relatively few infants in our study, since E faecalis infection has been shown to be more common in infantile endocarditis. 9 Relatively rare bacteria were found in some of our recent IE cases.…”
Section: Pathogensmentioning
confidence: 75%
See 3 more Smart Citations
“…1,4,[9][10][11] In our study, there was only 1 case of Enterococcus faecalis endocarditis (2%), compared with 7% to 16% reported in other series. 4,9,11 This may be due to the relatively few infants in our study, since E faecalis infection has been shown to be more common in infantile endocarditis. 9 Relatively rare bacteria were found in some of our recent IE cases.…”
Section: Pathogensmentioning
confidence: 75%
“…This trend in rheumatic heart disease has been shown in several other case series. 4,[8][9][10][11] A major risk factor for IE in patients with CHD is prior surgical intervention. In our study, there was a history of cardiovascular surgery in 34% of pa- …”
Section: Demographic Characteristics and Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations
“…It is a significant cause of morbidity and mortality in children and adolescents despite advances in the management and prophylaxis of the disease with antimicrobial agents [2][3][4][5]. Although IE is relatively uncommon in children compared with adults, accounting for 0.5−0.8 cases per 1,000 pediatric admissions [1][2][3][4][5], the incidence of pediatric IE is believed to be increasing [1]. This is due in part to improved survival among children who are at risk for IE, such as those with congenital heart disease (CHD) and hospitalized newborn infants [1][2][3][4].…”
mentioning
confidence: 99%